PEMORALITASAN SEBAGAI POLA DASAR PENGEMBANGAN KEBIJAKAN DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Madja, I Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
There is a term indicates ‘long life education’. It is meant that the human being as a primary creature in this life, and as long as he excis in this world, should motivate themselves to learn and get the science more than before. This term has permanently become a part of various education issues. Science’s progress recently trend to influent not even the world education, but the progress of technology also comes with it. The information progress as one of some indicators of science technology progress, is also taking a part in it. The acces that is prepared in various media, /give wide opportunity used in fullfilingng the information need. Education and learning are so much important in the human life. Both are intergrated as a perfectly unite, can not be spareted one each others. They must be in the form of harmonization. The learning process does not tranferisation’s problem and concentration of science only, but the education should be regarded as an aspect that is able to support the learning process. The knowledge that is obtained by students, if it is not supported by the educative things, makes either as student or an educated people trend to be immoralize, lack their spiritual, and phisological skill. For the future, the successful of education and learning are surely needed for the wisdom development moralization in constructing the carracter’s student. In Hindu’s perspective, it can be analized by value theory. Key words: Moralizement, Basic system, Wisdom development, Student’s caracter Construction